2015
DOI: 10.1097/ftd.0000000000000126
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Everolimus QMS Immunoassay on Architect ci4100 and Liquid Chromatography/Mass Spectrometry

Abstract: The everolimus QMS immunoassay, using the Architect ci4100 analyzer, had a significant positive bias compared with LC-MS/MS, with a wide range between the limits of agreement. The lack of agreement may result in inadequate everolimus dose adjustments, suggesting that the QMS assay cannot be used interchangeably with the LC-MS/MS method for therapeutic everolimus monitoring in organ-transplanted patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 9 publications
1
4
0
Order By: Relevance
“…Nevertheless, a previous study had observed a positive bias of 11% of the QMS assay compared to LC-MS/MS 15 . Such a positive bias was confirmed by two more recent studies 16,17 . However, these were single laboratory studies and sample quality and storage conditions were not as rigorously controlled as in the present study.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Nevertheless, a previous study had observed a positive bias of 11% of the QMS assay compared to LC-MS/MS 15 . Such a positive bias was confirmed by two more recent studies 16,17 . However, these were single laboratory studies and sample quality and storage conditions were not as rigorously controlled as in the present study.…”
Section: Discussionsupporting
confidence: 61%
“…However, these were single laboratory studies and sample quality and storage conditions were not as rigorously controlled as in the present study. While the present study was mostly based on samples from kidney transplant patients, these studies 16,17 included a relatively large number of samples from liver and lung transplant patients.…”
Section: Discussionmentioning
confidence: 99%
“…This can be understood considering the lack of agreement between various IAs despite manufacturers tracing the results to LC-MS/MS (their own reference) as well as between a single IA (QMS/EVER) and several different LC-MS/MS methods. 15,[27][28][29][30][31][32] Therefore, the importance of agreement with LC-MS/MS in evaluating the true direction of bias between IAs should be reconsidered with respect to the characteristics of the "reference" method adopted (eg, using commercially available IVD-CE-labeled or in-house gravimetrically prepared calibrators, extraction with methanol or acetonitrile). 4 Second, this study was designed as a short-term verification study.…”
Section: Discussionmentioning
confidence: 99%
“…et al with 169 patient samples, mean everolimus concentration produced by the QMS everolimus test was found to be 31.2% higher than that determined by LC-MS/MS [19]…”
mentioning
confidence: 90%